2012
DOI: 10.1038/tp.2012.44
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated aggression and decreased anxiety in mice deficient in brain serotonin

Abstract: Serotonin is a major neurotransmitter in the central nervous system (CNS). Dysregulation of serotonin transmission in the CNS is reported to be related to different psychiatric disorders in humans including depression, impulsive aggression and anxiety disorders. The most frequently prescribed antidepressants and anxiolytics target the serotonergic system. However, these drugs are not effective in 20–30% of cases. The causes of this failure as well as the molecular mechanisms involved in the origin of psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
203
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(228 citation statements)
references
References 79 publications
17
203
1
2
Order By: Relevance
“…Both Tph2 -/-and SERT -/-mice have been established on a pure C57BL/6 genetic background [21]. Animals were 10 to 12 weeks old at the time of sacrifice.…”
Section: Animalsmentioning
confidence: 99%
“…Both Tph2 -/-and SERT -/-mice have been established on a pure C57BL/6 genetic background [21]. Animals were 10 to 12 weeks old at the time of sacrifice.…”
Section: Animalsmentioning
confidence: 99%
“…26 Mosienko and colleagues reported that TPH2 −/− mice displayed increased immobility in the FST but not on the TST. 29 The possibility exists that moderate reductions in brain 5HT, versus the more drastic depletions seen in PET-1 and TPH2 −/− mice, would reveal a depression-like phenotype.…”
Section: Va Author Manuscriptmentioning
confidence: 99%
“…26 Mosienko and colleagues reported that TPH2 −/− mice displayed increased immobility in the FST but not on the TST. 29 The possibility exists that moderate reductions in brain 5HT, versus the more drastic depletions seen in PET-1 and TPH2 −/− mice, would reveal a depression-like phenotype.Testing of this possibility has been done using mice with partial reductions in TPH2 expression. For instance, Beaulieu and colleagues 47 generated a knockin mouse line that Zhang and colleagues 51 reported a functional single nucleotide polymorphism in the mouse TPH2 gene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Serotonin depletion in transgenic mouse models also results in altered behavior such as exaggerated aggressiveness that goes along with reduced anxiety (Mosienko et al, 2012) and increased impulsivity (Angoa-Perez et al, 2012 Gaspar, 2012, Mosienko et al, 2014); that may reflect unchanged baseline neurogenesis, but also indicates an uncoupling of the behavioral mechanisms governing depression and serotonin levels in a unique homeostasis created over time. Compensatory mechanisms seem to occur in life-long serotonin depletion and the replacement of this neurotransmitter by expression or activity of other neurotransmitter systems has been debated (Beckman and Santos, 2013).…”
Section: Animal Models: Addressing the Controversy Of Serotonin's Rolmentioning
confidence: 99%